A low feed-through 3D vacuum packaging technique with silicon vias for RF MEMS resonators. (21st November 2016) - Zhao, Jicong; Yuan, Quan; Kan, Xiao; Yang, Jinling; Yang, Fuhua
Abstract: This paper presents a wafer-level three-dimensional (3D) vacuum packaging technique for radio frequency microelectromechanical systems (RF MEMS) resonators. A Sn-rich Au–Sn solder bonding is employed to provide a vacuum encapsulation as well as electrical conductions. Vertical silicon vias are micro-fabricated by glass reflow process. The optimized grounding, via pitch, and all-round shielding effectively reduce feed-through capacitance. Thus the signal-to-background ratios (SBRs) of the transmission signals increase from 17 dB to 20 dB, and the quality factor ( Q ) values of the packaged resonators go from around 8000 up to more than 9500. The measured average leak rate and shear strength are (2.55  ±  0.9)  ×  10 −8 atm-cc s −1 and 42.53  ±  4.19 MPa, respectively. Furthermore, thermal cycling test between  −40 °C and 100 °C and high temperature storage test at 150 °C show that the resonant-frequency drifts are less than  ±7 ppm. In addition, the SBRs and the Q values have no obvious change after the tests. The experimental results demonstrated that the proposed encapsulation technique is well suited for the applications of RF MEMS devices.